Philologia versus philosophia - Verhaart, F (2016)
The aim of this thesis is to provide a revaluation of the so-called Quarrel of the Ancients and the Moderns at the turn of the eighteenth century, with particular reference to Britain, France, and the Dutch Republic. The Quarrel split the European Republic of Letters into two camps: those who thought the achievements of the classical world had been surpassed in the seventeenth century and the study of Latin and Greek had become pointless, and those who thought the classical inheritance remained invaluable. In this thesis, the Quarrel will be examined from the point of view of those who believed in the continued significance of the classical inheritance but who were divided among themselves over how it was best protected: should its study be turned into a purely scholarly pursuit, knowledge for its own sake, or should its study be promoted as a source of wisdom and moral example? This opposition between two approaches to the classical inheritance is then used to analyse and explain a number of key developments in the period under review. These include the reception of Renaissance humanism at the turn of the eighteenth century, the professionalisation of scholarship, the rise of the distinction between form and content in aesthetic thought, and the popularisation of classical culture. Although the debate between these two approaches primarily focused on the issue of the classical inheritance, it will also help us to gain a better understanding of the Republic of Letters tout court, its membership, prejudices and interests in the era of the so-called Crise de conscience européenne. The United Provinces is the ideal starting-point for such a study, since it has recently been argued at length by Jonathan Israel in his Radical Enlightenment (2001) that Holland at the turn of the eighteenth century gave birth to the radical, atheistic Enlightenment. This thesis will test the plausibility of Israel’s grandiose claims and bring the Dutch pre-Enlightenment back to earth. At the same time this thesis will help us to better understand the United Provinces intellectual connections with England and France and show the important role played by the Querelle in the early Enlightenment. It was not on the periphery, as we have always thought, but at its heart.